Preliminary Values of Diagnostic Reference Level for Selected X-Ray Examinations in Indonesia - E. Hiswara; H. Prasetio; D. Kartikasari; N. Nuraeni; K.Y.P. Sandy (Atom Indonesia, 2016)
The diagnostic reference levels form an efficient, concise, and powerful standard for optimizing the radiation protection of a patient. With an aim to contribute toward the establishment of the Indonesian National Diagnostic Reference Levels (NDRLs), a nationwide survey of the entrance surface doses received by adult patients during the most typical X-ray examinations has been performed. A number of 44 hospitals in 21 cities located in Java, Bali, Sumatera, Kalimantan, and Sulawesi islands were selected randomly to participate in this survey. Eight most common adult X-ray examinations in 13 projections, as well as four children X-ray examinations in six projections, were included in the list of procedures under consideration. Hospitals of different sizes and levels using different X-ray machines were represented in the survey. Standard thermoluminescence dosemeters were applied to measure entrance surface dose (ESD). A total of 1493 patients, consisting of 1208 adults and 285 children, were included in this study. The data were analyzed statistically and the minimum, median, mean, maximum, first quartile, and third quartile values of ESDs were reported. The ESDs calculated (third quartile) for adults varied from 0.18 mGy (for extremities AP) to 5.84 mGy (for lumbar spine LAT), and for children they varied from 0.16 mGy (for chest AP/PA) to 1.46 mGy (for skull AP/PA). Considering the geographic spread and size of Indonesia, those third quartile values calculated can only be regarded as preliminary DRL values for Indonesia. Compared with data from other countries, the calculated ESDs in this study are in general lower than the ESDs in those countries.Received: 16 November 2015; Revised: 27 April 2016; Accepted: 9 May 2016